Bioethics and the humanization of care: An approach to individual-oriented care - Mancera-Guzmán, Claudia Liliana (2025)
Bioethics and the humanization of care represent fundamental pillars for transforming health care, promoting a vision centered on the dignity, rights and integral wellbeing of the patient. Traditionally, biomedical models have prioritized the disease, relegating the human dimension of the care process. However, the individual-centered care model redefines this perspective by situating the patient as an active subject, with his or her own values, emotions and sociocultural contexts. Bioethics, as a normative discipline, establishes essential principles such as autonomy, beneficence and justice, guaranteeing ethical and respectful medical practice. For its part, the humanization of care requires a modification of interaction in the health professional-patient relationship, emphasizing empathy, communication and shared responsibility in making health determinations at the individual level. The integration of these principles in the education of human talent in health and in the design of health policies is crucial to consolidate more just, equitable and person-centered health systems. This article analyzes the intersection between bioethics and the humanization of care, highlighting their role in advancing the quality of care and in promoting a model of care that recognizes individuality and respect for each individual.